2013
DOI: 10.1159/000350313
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal and Paternal Body Mass Index and Offspring Obesity: A Systematic Review

Abstract: Background/Aims: It has been hypothesized that the intrauterine environment is an independent factor in obesity development. If so, the maternal effect is likely to be a stronger influencing factor (‘fetal overnutrition hypothesis'). We aimed to systematically evaluate the associations of offspring body mass index (BMI, or adiposity) with pre-pregnancy BMI (or adiposity) of the mother and the father. Methods: The Medline, Embase and Cochrane Library databases were searched in March 2012. Results: Seven cohort … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
110
3
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(128 citation statements)
references
References 16 publications
12
110
3
3
Order By: Relevance
“…The key assumption of the negative control design is that both exposures share the same postnatal environmental and genetic confounders. A systematic review (8) of such studies, together with subsequent studies not included in the review (9)(10)(11)(12), have found only limited support for specific effects of maternal adiposity on offspring adiposity beyond birth. To our knowledge, similar causal inference techniques have not yet been applied to study maternal effects of adiposity in pregnancy on other aspects of offspring health.…”
Section: Introductionmentioning
confidence: 99%
“…The key assumption of the negative control design is that both exposures share the same postnatal environmental and genetic confounders. A systematic review (8) of such studies, together with subsequent studies not included in the review (9)(10)(11)(12), have found only limited support for specific effects of maternal adiposity on offspring adiposity beyond birth. To our knowledge, similar causal inference techniques have not yet been applied to study maternal effects of adiposity in pregnancy on other aspects of offspring health.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14][15][16] Several systematic reviews and meta-analyses confirm the association of pre-pregnancy overweight/obesity with the risk for high birth weight (HBW), large-for-gestational-age (LGA) neonates, macrosomia and subsequent offspring overweight/ obesity, 17,18 while others provide limited evidence to support the aforementioned association. 19 Furthermore, there are still important gaps in the literature that need to be assessed such as the pathophysiological mechanisms involving the maternal obesity effects with adverse pregnancy outcomes and future metabolic consequences for the fetus; the development of markers or algorithms for early prediction (from the beginning of pregnancy) of these adverse pregnancy outcomes, such as gestational diabetes and preeclampsia; establishment of criteria and cor-responding management for the pregnancy-acquired weight in specific groups at risk (e.g. pregnant women with pre-pregnancy BMI >40).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal obesity is currently one of the leading factors predicting childhood obesity (24). Maternal obesity is associated with abnormal feto-placental function (25), offspring obesity risk (24), and increased disease risk in general.…”
Section: Maternal Obesitymentioning
confidence: 99%
“…Maternal obesity is currently one of the leading factors predicting childhood obesity (24). Maternal obesity is associated with abnormal feto-placental function (25), offspring obesity risk (24), and increased disease risk in general. Although maternal high-fat (HF) diet models in animals have made significant advances in our understanding of the underlying mechanisms, linking maternal obesity with offspring obesity and metabolic dysfunction which one (or combination) of the identified signaling pathways is best for targeted interventions to reduce childhood and adolescent obesity and metabolic compromise is as of yet, unclear.…”
Section: Maternal Obesitymentioning
confidence: 99%